Normal Rectal Filling Sensations in Patients with an Enlarged Rectum - Verkuijl, Sanne J. (Dig Dis Sci, 2018)
BACKGROUND: Increased rectal volume is believed to be associated with diminished rectal sensation, i.e., rectal hyposensitivity. AIMS: To demonstrate that patients with increased rectal volumes do not automatically have diminished rectal filling sensations. METHODS: We, retrospectively, observed 100 adult patients with defecation problems, and 44 healthy controls who had undergone anorectal function tests. Using the balloon retention test, we analyzed the distribution of rectal volumes and pressures at different rectal filling sensation levels. RESULTS: We found variance in the distribution of rectal volumes at all levels, while rectal pressures showed a normal distribution. We found no correlation between rectal volumes and pressures (constant sensation, r = 0.140, P = 0.163, urge sensation, r = − 0.090, P = 0.375, and maximum tolerable volumes, r = − 0.091, P = 0.366), or when taking age and sex into account. The findings for the patient group were congruent with those for the control group. CONCLUSIONS: Participants with increased rectal volumes do not experience increased rectal pressures at any sensation level. This finding, combined with the knowledge that rectal pressure triggers rectal filling sensation, indicates that rectal filling sensations in patients with increased rectal volumes are not diminished. Therefore, “rectal hyposensitivity” should be reserved for patients with increased rectal pressure thresholds, and not for “abnormally” increased rectal volume thresholds.